Presenteeism - (Not) new phenomenon in the occupational environment - Agata Wężyk; Dorota Merecz (Nofer Institute of Occupational Medicine, 2013)
Presenteeism, understood as being at work while ill, is not a new phenomenon. However, not long ago it has become an object of researchers' interest. Formerly, they focused mainly on absenteeism. In general, presenteesim is perceived as negative and very costly for employers. The majority of scientific studies refer to the problem of employees' productivity reduced due to their attending work despite being ill, but the knowledge about presenteeism's causes and effects (other than decreased productivity) for both, the employee and the organisation, is still very limited. Especially in Poland there are very few scientific reports on this issue. However, the paper on presenteeism published recently (the 3/2013 issue of this Journal) defined this phenomenon as a noneffective presence at work. The authors postulate to avoid pejorative connotation of this term by equating presenteeism with loss of productivity, and to separate this phenomenon from its possible negative and positive consequences. Thus, this paper aims at presenting current state of the art on this phenomenon, including such issues as definitional problems, measures and frequency of presenteeism, as well as its causes and consequences. In this paper presenteeism is presented in a wider perspective of its individual and contextual determinants. Med Pr 2013;64(6):847-861